STRATEGY AND SUSTAINABILITY OF BAITUL MAAL WAT TAMWIL IN THE DISRUPTION ERA: EXPERIENCE FROM LOMBOK WEST NUSA TENGGARA - Masud, Riduan; M. Syamsurrijal (Online Journal of Islamic Management and Finance (OJIMF), 2024)
The services of Islamic financial institutions known as Baitul Mal Wat Tamwil intended to help low-income communities improve their standard of living, have created economic defense for the community in the era of technological disruption. The research aims to investigate Baitul Mal Wat Tamwil’s resiliency strategy in the disruption age. In-depth interviews, literature reviews, and observations were the methods used to collect the data for this investigation. The acquired data has been combined and subjected to descriptive qualitative analyses. In the disruption era, it will be crucial for Baitul Maal Wat Tamwil to stay ahead of emerging trends and technologies in the financial industry. This will require a proactive approach to innovation and a willingness to adapt to changing market conditions. By embracing digital transformation and exploring new business models, the organization can position itself as a leader in the industry and continue to thrive in the face of disruption. Additionally, focusing on sustainability and social responsibility will be essential for maintaining a positive reputation and attracting socially conscious customers. Overall, by staying agile and forward-thinking, Baitul Maal Wat Tamwil can navigate the challenges of the disruption era and emerge more vital than ever before